Isolating adverse effects of glucocorticoids on the embryonic cardiovascular system. Issue 7 (5th June 2020) - Teulings, Noor E. W. D.; Garrud, Tessa A. C.; Niu, Youguo; Skeffington, Katie L.; Beck, Christian; Itani, Nozomi; Conlon, Fiona G.; Botting, Kimberley J.; Nicholas, Lisa M.; Ashmore, Thomas J.; Blackmore, Heather L.; Tong, Wen; et al.
Abstract: Antenatal glucocorticoid therapy reduces mortality in the preterm infant, but evidence suggests off‐target adverse effects on the developing cardiovascular system. Whether deleterious effects are direct on the offspring or secondary to alterations in uteroplacental physiology is unclear. Here, we isolated direct effects of glucocorticoids using the chicken embryo, a model system in which the effects on the developing heart and circulation of therapy can be investigated, independent of effects on the mother and/or the placenta. Fertilized chicken eggs were incubated and divided randomly into control (C) or dexamethasone (Dex) treatment at day 14 out of the 21‐day incubation period. Combining functional experiments at the isolated organ, cellular and molecular levels, embryos were then studied close to term. Chicken embryos exposed to dexamethasone were growth restricted and showed systolic and diastolic dysfunction, with an increase in cardiomyocyte volume but decreased cardiomyocyte nuclear density in the left ventricle. Underlying mechanisms included a premature switch from tissue accretion to differentiation, increased oxidative stress, and activated signaling of cellular senescence. These findings, therefore, demonstrate that dexamethasone treatment can have direct detrimental off‐target effects on the cardiovascular system in the developing embryo, which are independent of effects on the mother and/or placenta.